Development of a Multifunctional Benzophenone Linker for Peptide Stapling and Photoaffinity Labelling. (16th March 2016) - Wu, Yuteng; Olsen, Lasse B.; Lau, Yu Heng; Jensen, Claus Hatt; Rossmann, Maxim; Baker, Ysobel R.; Sore, Hannah F.; Collins, Súil; Spring, David R.
Abstract: Photoaffinity labelling is a useful method for studying how proteins interact with ligands and biomolecules, and can help identify and characterise new targets for the development of new therapeutics. We present the design and synthesis of a novel multifunctional benzophenone linker that serves as both a photo‐crosslinking motif and a peptide stapling reagent. Using double‐click stapling, we attached the benzophenone to the peptide via the staple linker, rather than by modifying the peptide sequence with a photo‐crosslinking amino acid. When applied to a p53‐derived peptide, the resulting photoreactive stapled peptide was able to preferentially crosslink with MDM2 in the presence of competing protein. This multifunctional linker also features an extra alkyne handle for downstream applications such as pull‐down assays, and can be used to investigate the target selectivity of stapled peptides. Abstract : Three functionalities, one linker : A novel multifunctional linker was designed for peptide stapling and photoaffinity labelling. This approach uses a benzophenone moiety for crosslinking and an additional alkyne handle for subsequent pull‐down assays. The alternative labelling technique was applied to the p53/MDM2 interaction as proof of principle.